Influence of 2D CuxAl(100-x) electrodes on the CuxAl(100-x)/Cu21(SiO2)79/W memristive device - Gu, Bin; Wen, Guangyu; Zhang, Bo; Rodriguez Pereira, Jhonatan; Wágner, Tomáš (World Scientific Publishing Co., 2024)
In recent years, 2D metal nanomaterials have emerged as a novel class of 2D materials owing to their unique physiochemical properties. In this paper, memristive devices (Al-x((100-x))(BE)/Cu-21(SiO2)(79)/W(TE)) were fabricated utilizing 2D CuxAl(100-x) mate-rials with different compositions as electrodes. After exfoliation by sonication, the minimum thickness of the freestanding single layer of 2D CuxAl(100-x) was only 1.5 nm. Furthermore, the distribution of SET thresholds was determined by the composition of the 2D CuxAl(100-x) materials. The results suggest that the SET and RESET thresholds can be adjusted according to the composition of the 2D CuxAl(100-x) materials. The application of 2D metals as electrodes is promising for miniature memristive devices
Vliv 2D elektrod CuxAl(100-x) na memristivní zařízení CuxAl(100-x)/Cu21(SiO2)79/W
Keywords: 2D materials; memristive device; 2D materiály; memrisistivní zařízení